Time And Age Specific Mating Success Of Bumblebee (Bombus Terrestris L.) Reared At Different Photoperiodic Regimes - Amin, MR; Kwon, VJ (Bangladesh Journal of Agricultural Research, 2011)
In this study, mating success of bumblebee, Bombus terrestris was recorded by five age groups of queens viz. 3, 5, 7, 9, and 11 days old, and the males were two days older than each age group of queens. Newly emerged males and queens were collected from different colonies and they were reared under four photoperiods e.g., L0:D24, L8:D16, L16:D8, and L24:D0 for observing the mating activities. Three days old queens with 5 days old males showed the lowest mating success at all photoperiodic regimes. Most of the couples mated within first 15 minutes of pairing and mating success increased with increasing duration of mating exposure. At the L0:D24 and L8:D16 photoperiodic regimes 9 days old queens with 11 days old males had the highest mating success (65.4 ± 3.3 and 85.0 ± 2.3%, respectively) whereas at L16:D8 and L24:D0 photoperiodic conditions, the highest mating success occurred when 7 days old queens paired with 9 days old males (92.1 ± 1.7 and 76.3 ± 3.2%, respectively). These results indicate that rearing of bees at different light regimes, age of bees and duration of mating exposure had significant effect on mating success of B. terrestris. Keywords: Age; Bombus terrestris; mating; photoperiod; time. DOI: http://dx.doi.org/10.3329/bjar.v36i1.9225 BJAR 2011; 36(1): 13-20